2009
DOI: 10.2134/jeq2008.0205
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Accumulation below Cattle Feedlot Pens in Kansas

Abstract: Waste excreted on cattle (Bos taurus) feedlot pens is a source of N and other nutrients that could potentially leach into soil and negatively impact local groundwater quality. Analyses of soil chemical and physical properties beneath active open air feedlot pens were conducted at four Kansas locations to determine nutrient accumulation. Results were compared to estimated nutrient deposition, and remediation implications were considered. The surface concentrations of NH(4)-N, organic N, organic C, Cl(-), and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
5
18
0
Order By: Relevance
“…This may indicate that during cool weather when volatilization is limited by temperature, ammonium occupies a relatively stable proportion of exchange sites. Vaillant et al [20] sampled pen surfaces at four different feedlots in Kansas, organic N ranged from 500-22,000 mg·kg in only one pen and were much more frequently in the range reported in this study. Cole et al [21] measured pen surface chemical characteristics at three feedlots in Texas in all four seasons.…”
Section: Nutrient Analysismentioning
confidence: 47%
See 1 more Smart Citation
“…This may indicate that during cool weather when volatilization is limited by temperature, ammonium occupies a relatively stable proportion of exchange sites. Vaillant et al [20] sampled pen surfaces at four different feedlots in Kansas, organic N ranged from 500-22,000 mg·kg in only one pen and were much more frequently in the range reported in this study. Cole et al [21] measured pen surface chemical characteristics at three feedlots in Texas in all four seasons.…”
Section: Nutrient Analysismentioning
confidence: 47%
“…Summary statistics for pH measurements for all sampling dates and treatments are presented in Table 1. Vaillant et al [20] reported surface pH around 8.5 for feedlots in Kansas, Cole et al [21] report a yearly average surface pH of 7.7 for feedyards in Texas, and Cole and Todd [22] observed an annual mean pH of 7.89 from air-dried manure from Texas feedlots. Working in Nebraska, Gilbertson et al [23] reported average pH of 7.6 and 6.6 for two different stocking densities.…”
Section: Nutrient Analysismentioning
confidence: 99%
“…Lastly, feedlot status-of-use (Vaillant et al 2009) and age of the site (Zhu et al 2004) are important considerations related to possible environmental degradation and contamination, with older and abandoned sites posing a greater risk because of diminished management and typically fewer environmental protection regulations that were active during operation. Mitigating "legacy" P derived from agricultural sources presents challenges because the traditional conservation approach, reducing soil erosion and transport to surface water, may not provide a sufficiently robust management strategy (Kleinman et al 2011).…”
Section: Research Articlementioning
confidence: 99%
“…Thus, for even small feedlots, the nutrients generated can easily total in the tens of thousands of kilograms. While much N is lost to the atmosphere as ammonia (Hristov et al 2011) and some of the N and P is spread and broadcast beyond the confines of the feedlot (Everett and Vickery 2005), a large portion may be transported vertically and then laterally after leaching into soils that underlie the facility (García et al 2012;Vaillant et al 2009;Chang and Entz 1996). In this report, we suggest that feedlots may create "hot spots" of N and P that can serve as a potentially long-term source of nutrients, which can lead to downstream eutrophication, harm nearby wetlands, and degrade natural plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted on FL systems have found that ammonium concentrations to be as high as 100 to 250 mg N kg -1 at 10 cm soil depth (Ball et al, 1979;Carran et al, 1982;Sherlock and Goh, 1985) and from 500 to 1000 mg N kg -1 in the surface 2.5 cm (Vallis et al, 1985), which were higher than those normally found on grasslands with no intensive livestock production (Norris, 2000). Ammonium is not a very mobile constituent in soils because it participates in cation exchange, but upon exchange site saturation, NH 4 -N can then be leaching (Vaillant et al, 2009).…”
Section: Introductionmentioning
confidence: 99%